Design of Automatic Body Mass Index Measurement and Centralization Data Collection - Airlangga, Primaadi; Kurniawan, Dandi (KH. A. Wahab Hasbullah University, 2024)
Body mass index is one of the indicators used in assessing and measuring a person's nutritional and health status which is important to know and understand for human life. Technological developments in today's modern era have touched almost all sectors of life to improve performance, in terms of effectiveness and efficiency as well as convenience for users, including health facilities. The design of a centralized body index measuring device was created to alleviate and overcome various problems that occur in health facilities regarding patient body mass index data which are often inaccurate because the data is missing or does not match between one table and another. This body index measuring device includes microcontroller, RFID, HX711 Load Cell digital scales, height measuring instrument, website and smartphone. All of data from sensor readings will be displayed via a 16x2 LCD, stored on a server, and displayed via a website and user’s smartphone.